Preparation and Application of Photonic Crystal Paints with Tunable Structural Colors. Issue 9 (16th March 2020) - Wu, Yu; Liu, Guojin; Li, Hui; Han, Penshuai; Cheng, Jinyu; Zhou, Lan
Abstract : A simple and fast paint drawing method is applied in fabricating patterned photonic crystals (PCs) on white paper substrates. The paints with structural colors are simply fabricated using monodispersed black disperse dye@poly(styrene–butyl acrylate–methacrylate) (P(St–BA–MAA)) microspheres via a rapid centrifugal treatment. Specifically, the centrifugal speeds and centrifugal times of dye@P(St–BA–MAA) microspheres are systematically optimized, and the apparent colors of prepared paints are simply characterized, and then the paints are used to fabricate photonic crystal patterns (PCPs) by paintbrushes. It is confirmed that the suitable paints can be prepared at 8000 rpm centrifugal speed and 30 min centrifugal time. The prepared paints display bright and iridescent structural colors, which indicates that the dye@P(St–BA–MAA) microspheres of paints undergo a certain degree of self‐assembly during the driving of centrifugal forces. The prepared paints fabricate 3D PCPs with bright and iridescent structural colors within 10–20 s. Moreover, when the diameter of microspheres decreases or the viewing angle increases, the resultant structural colors produce a blue shift according to Bragg's diffraction law. It is believed that the paints for fabricating PCPs with tunable structural colors have wide applications in painting fields. Abstract : Paints with structural colors are fabricated using poly(styrene–butyl acrylate–methacrylate) (P(St–BA–MAA)) microspheres via a rapid centrifugation procedure. Specifically, the centrifugal processing parameters of P(St–BA–MAA) microspheres, arrangement state of microspheres in photonic crystal (PC) paints, and structural colors of PC patterns are optimized. The prepared paints present wide applications in painting fields.